Synthesis, characterizations of pure and Co2+ doped iron oxide nanoparticles for magnetic applications. (2022) - Subash, M.; Chandrasekar, M.; Panimalar, S.; Inmozhi, C.; Uthrakumar, R.
Abstract: In this research, we investigate the effects of pure and cobalt substitution on the size development, crystal erection, and attractive possessions of -Fe2O3 nanoparticles, which were synthesised using the Sol-Gel process. X-ray Diffraction (XRD), scanning electron microscopy with energy dispersive X-ray spectroscopy (SEM-EDX), and Fourier Transform Infrared Spectroscopy (FTIR) were used to analyse crystalline nature, magnitude, outline, and chemical composition of iron oxide (Fe2O3) nanoparticles (FT-IR). The change in direct band gaps is demonstrated by UV-Visible spectroscopy and compared to XRD findings. Furthermore, an XRD spectrum survey indicated that the material had a cubic structure. Scanning Electron Microscopy may be cast-off to characterise the morphologies and structures of iron oxides. The use of EDX to analyse elements revealed that cobalt doping had been successful. At room temperature, magnetic characteristics were resolute using a Vibrating Sample Magnetometer (VSM). Magnetic tests revealed that, when compared to pure and cobalt-doped nanoparticles, there is a significant difference. Furthermore, the doping content has a significant impact on magnetic characteristics.